DIMENSI SPIRITUALITAS DALAM KISAH PEWAYANGAN DEWA RUCI - Hadyu Kharis Al Asrofi; Rizal Al Hamid (Sanjiwani: Jurnal Filsafat, 2025)
The wayang stories hold profound spiritual meaning in Javanese culture, one of which is the story of Dewa Ruci. This narrative depicts Bima's spiritual journey in his quest for the essence of life and enlightenment. Utilizing textual analysis and symbolism, this study examines the dimensions of spirimality embedded within the Dewa Ruci tale, including ethical values, philosophy, and spiritual teachings that remain relevant to modern life. Throughout his jourmey, Bima encounters various obstacles that represent humanity arch for truth and wisdom. Through his encounter with Dewa Ruci, he gains a deep understanding of the relationship berween humans, the universe,and the Divine. This research highlighrs the symbolic meaning of the story and how its teachings can inspire contemporary sociery. Consequentty, the Dewa Ruci tale is not merely a culural heritage but also a profound reflection of humanity's quest for spiritual fulfillment and the pursuit of a meaningful life.